2022
DOI: 10.1007/s00203-022-03117-z
|View full text |Cite
|
Sign up to set email alerts
|

Cationic polymer contributes to broaden the spectrum of vancomycin activity achieving eradication of Pseudomonas aeruginosa

Abstract: Vancomycin (VAN) is unable to penetrate the outer membrane of Gram-negative bacteria and reach the target site. One approach to overcome this limitation is to associate it with compounds with permeabilizing or antimicrobial properties. EudragitE100® (Eu) is a cationic polymer insufficiently characterized for its potential antimicrobial action. Eu-VAN combinations were characterized, the antimicrobial efficacy against Pseudomonas aeruginosa was evaluated and previous studies on the effects of Eu on bacterial en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…It is, therefore, justified to conclude that this was, too, due to the synergy of EE and OCT. In accordance with our results, the bactericidal effect of EE against another Gram-negative Pseudomonas aeruginosa was previously reportedin works by Romero et al and Corti et al , Bacterial membrane damage, i.e., permeabilization of bacterial envelopes and morphological alterations, were observed, but there was none or little cell death in contact with drug-free EE. However, in both cases, the killing effect obtained using the EE drug delivery system was not observed with the drug itself, which was assigned to its cationic nature that contributed to interactions between the incorporated drug and the negatively charged bacterial cell.…”
Section: Resultssupporting
confidence: 93%
“…It is, therefore, justified to conclude that this was, too, due to the synergy of EE and OCT. In accordance with our results, the bactericidal effect of EE against another Gram-negative Pseudomonas aeruginosa was previously reportedin works by Romero et al and Corti et al , Bacterial membrane damage, i.e., permeabilization of bacterial envelopes and morphological alterations, were observed, but there was none or little cell death in contact with drug-free EE. However, in both cases, the killing effect obtained using the EE drug delivery system was not observed with the drug itself, which was assigned to its cationic nature that contributed to interactions between the incorporated drug and the negatively charged bacterial cell.…”
Section: Resultssupporting
confidence: 93%
“…Although a reduction between 1.5 and 3.5 log 10 of the viable count was observed after brief periods of exposure to Eu alone (Figure 1C,D), depending on the polymer concentration and exposure time analyzed, the counts recovered to the level of the untreated control after 24 h, as already reported in previous studies. 35,36 The results indicate that the three combinations Eu + TMPyP exhibited improved photoinactivation against P. aeruginosa (Figure 1C,D), with a significant reduction in the viable count with respect to their components evaluated individually after 30 min of irradiation (p < 0.05). At shorter irradiation time, only the highest concentration of Eu tested in combination with TMPyP exhibited significant differences.…”
Section: Effect Of Eudragit E100® (Eu) On Apdi Of P Aeruginosamentioning
confidence: 96%
“…An accurately weighed quantity of polymer was dissolved in a minimum volume of acetone; and 1.0 N HCl (volume equivalent to 50% of the amino groups of the polymer) was subsequently added to overcome solubility limitations, as previously reported. [35][36][37] After evaporating the solvent, the obtained powder (Eu) was used to prepare aqueous dispersions. Eu + TMPyP combinations were prepared by adding aliquots of stock solution dilutions of TMPyP to aqueous dispersions of Eu.…”
Section: Photosensitizer and Cationic Polymermentioning
confidence: 99%
See 1 more Smart Citation
“…Manipulation of the sequence of hydrophobic and hydrophilic subunits of antimicrobial polymers is an important factor in achieving facial amphiphilicity for antibacterial activity. A recent study combining vancomycin with the cationic polymer Eudragit E100 ® (Eu) against P. aeruginosa showed that P. aeruginosa was eradicated within 3–6 h of exposure with this combination treatment [ 105 ]. Although bacterial envelope permeabilization and morphological changes after exposure to Eu were not sufficient to cause bacterial death, they allowed vancomycin to enter the target site, thereby enhancing the activity of an otherwise inactive vancomycin against P. aeruginosa .…”
Section: Organic Nanomaterialsmentioning
confidence: 99%